Climate proofing agricultual research investments - Jones, Peter G.; Jarvis, Andy; Hyman, Glenn G.; Beebe, Stephen E.; Pachico, Douglas H. (2007)
The case for impending climate change is now proven. Governments can decide, by their action or inaction, to what extent the change will occur; the International Agriculture Research Community (IARC) will have no say in this whatsoever. It is up to the IARC to try to maintain objectives in the face of the possible scenarios. In this paper we discuss the various types of agricultural research projects in terms of their time to fruition and the expected longevity of their results. We look at the information requirements for ensuring that project products have the necessary lifetimes to justify the investments in the research. We show that strategies differ depending on the type of research that is undertaken. Basic research into genetic traits and capacities within the available germplasm has to be planned in the long term with outcomes in mind. The vulnerability of the populations and agricultural systems that use developments from this basic research now places its priority setting in a changing climate and world concept. Ensuring that the germplasm is available for use has taken on a critical new importance with recent studies. Germplasm banks comprise a small fraction of what we will be relying on for the future. Well over 90% of useful genetic variability may still be in the wild. This has to be considered carefully in setting out research objectives. Plant breeders, who will put together the results of the basic research into useful packages, now have an uncertain target to aim for when regarding future climate conditions. They may not be able to choose their testing sites in present climates to target agricultural populations that will be using their products in the future. Agronomic and agricultural development projects face the most difficult task. How do we develop stable farming systems in an environment that is not only unstable, but also changing so slowly that the farmers cannot see, or even envisage, the changes. These are some examples of the problem. The paper sets out to categorise the types of research and information that will be necessary at all levels. We draw on experience from the CGIAR system and from CIAT in particular. We show that a number of software tools have been developed that can address some of these problems.